2013
DOI: 10.1088/0169-5983/45/6/061403
|View full text |Cite
|
Sign up to set email alerts
|

Flames in fractal grid generated turbulence

Abstract: Twin premixed turbulent opposed jet flames were stabilized for lean mixtures of air with methane and propane in fractal grid generated turbulence. A density segregation method was applied alongside particle image velocimetry to obtain velocity and scalar statistics. It is shown that the current fractal grids increase the turbulence levels by around a factor of 2. Proper orthogonal decomposition (POD) was applied to show that the fractal grids produce slightly larger turbulent structures that decay at a slower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 92 publications
1
51
0
Order By: Relevance
“…It is worth noting that if none of the corrections described in appendix A were applied, the results of experiment 3 would be systematically lower than those of experiment 4 (by a mean value of 63%). Similar conclusions apply to the flow scales reported in table 6. Values of the Kolmogorov length scale oscillate in an interval 0.10 − 0.14 mm, which is in good agreement with Gomes-Fernandes et al [18].…”
Section: Small-scale Propertiessupporting
confidence: 90%
See 2 more Smart Citations
“…It is worth noting that if none of the corrections described in appendix A were applied, the results of experiment 3 would be systematically lower than those of experiment 4 (by a mean value of 63%). Similar conclusions apply to the flow scales reported in table 6. Values of the Kolmogorov length scale oscillate in an interval 0.10 − 0.14 mm, which is in good agreement with Gomes-Fernandes et al [18].…”
Section: Small-scale Propertiessupporting
confidence: 90%
“…The derivation of the energy budget equations, presented in section 5, requires introducing set of assumptions (6). Some of them are rather trivial (e.g.ā =ā) but some may raise a concern, in particular those governing a l ,ã l a orã lãm .…”
Section: Validation Of the Energy Budget's Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the use of fractal cross grids led to a more than 100% increase in turbulence levels, with a potential for further increases, leading to a corresponding reduction in ratio of bulk to turbulent strain and thus enabling extended studies of turbulent flames in the opposed jet configuration. Subsequent studies include the structure of turbulence in lean premixed flames (Goh et al 2013a), the determination of scalar fluxes and conditional statistics (Goh et al 2014) and turbulent transport in flames approaching extinction (Goh et al 2015). In addition, studies using rod stabilisation (Soulopoulos et al 2013) and low-swirl combustion (Verbeek et al 2015) have appeared suggesting potentially wider application.…”
Section: Introductionmentioning
confidence: 99%
“…The approach permits the identification of five fluid states (reactant, combustion product, mixing, mildly reacting and flamelet fluids) and a range of Da numbers, from the conventional propagating flamelet regime well into the distributed reaction zone regime, are investigated. Böhm et al (2009) and Goh et al (2013aGoh et al ( , 2013bGoh et al ( , 2014 have shown that the combination of PIV and OH-PLIF can be used to obtain velocity-scalar statistics describing the dynamics of opposed jet flames approaching extinction and the techniques form the basis for the investigations reported here.…”
Section: Introductionmentioning
confidence: 99%